TEACHER TRAINING, CURRICULUM AND CHILDHOOD IN TRADITIONAL COMMUNITIES IN THE AMAZON - Fabiola Aparecida F. Damacena; Raquel Lopes (Universidad Nacional del Nordeste, 2021)
This paper discusses the possibility of implementing a new educational assistance policy for rural children through changes in the curriculum of teacher education courses. Thus, its main objective is to present evidence in order to enable paradigmatic changes in the sociopedagogical matrix of the educational processes of the future teachers, highlighting some aspects of a particular experience carried out between the years of 2015 and 2019 in the countryside of Brazilian Amazon, more specifically in the Southwest of Pará. The methodology used is characterized by the direct immersion in the context of the experience registered in this work as well as by participant observation and the reflection of records resulting from it. The most important results indicate an urgent need to reverse the logic of teacher education overcoming an abstract perspective based on universalized and colonizing assumptions as well as to bring the fundamentals of educational processes closer to the characteristics of the territory where they will be applied together with the involved subjects, with a view to prioritize the childhood to be assisted. In this sense, the dialogue with data leads to the unavoidable conclusion that it is urgent to base the curriculum of teacher educational courses on structural axes linked to pedagogical practice, sociocultural diversity and human rights.